2013
DOI: 10.1038/nchem.1612
|View full text |Cite
|
Sign up to set email alerts
|

Label-assisted mass spectrometry for the acceleration of reaction discovery and optimization

Abstract: Identification of new reactions expands our knowledge of chemical reactivity and enables new synthetic applications. Accelerating the pace of this discovery process remains challenging. We describe a highly effective and simple platform for screening a large number of potential chemical reactions in order to discover and optimize previously unknown catalytic transformations thereby revealing new chemical reactivity. Our strategy is based on labeling one of the reactants with a polyaromatic chemical tag, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…It has been noted previously that analyte detection by MALDI-TOF MS can be greatly enhanced by covalent attachment to a chromophore capable of absorbing the MALDI UV laser energy, which may account for the signal enhancement seen herein upon labeling with 1 . 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…It has been noted previously that analyte detection by MALDI-TOF MS can be greatly enhanced by covalent attachment to a chromophore capable of absorbing the MALDI UV laser energy, which may account for the signal enhancement seen herein upon labeling with 1 . 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…64 The IEDDA reaction of cyclic azadienes is a useful alternative to access heterocycles and carbocycles. 67 Interestingly, silver salts proved to be effective and could efficiently catalyse the cyclization of various N-alkylpyridinium iodides and N-alkylisoquinolinium iodides 56 with siloxyalkynes 55, which afforded the corresponding phenols and naphthols 57 in 55-98% yields (Scheme 24). 65 Very few examples of IEDDA reactions of cyclic azadienes catalysed by Lewis acids are known.…”
Section: Cycloaddition and Cyclizationmentioning
confidence: 99%
“…Polyaromatic moieties are most versatile in this regard because they have high molar absorptivity that allows efficient absorption of laser radiation and also for their facile ability to form molecular ions. Kozmin et al in a landmark paper first reported the use of pyrene as a polyaromatic MS tag and established a general and powerful method for reaction optimization and discovery with LALDI‐TOF‐MS . This method is unique due to its very different working principle.…”
Section: Label‐assisted Laser Desorption/ionization Mass Spectrometrymentioning
confidence: 99%
“…Following the work reported, a new LALDI‐MS based metal ion detection technique was reported . It has been demonstrated that the use of a polyaromatic probe with specific affinity toward an analyte allowed detection of the latter with LDI‐MS.…”
Section: Label‐assisted Laser Desorption/ionization Mass Spectrometrymentioning
confidence: 99%